Silver Diamine Fluoride 30% dan 38% Sebagai Bahan Pencegahan Karies Gigi Anak: A Scoping Review - Siti Tika Kamilla; Dhyani Widhianingsih; Sri Ratna Laksmiastuti (Fakultas Kedokteran Gigi Universitas Trisakti, 2022)
Background: Dental caries is the most common disease in children if ignored will cause various problems that quality of life. Therefore, it is very necessary to prevent early caries. The prevention of caries using Silver Diamine Fluoride is an effective option to prevent the development process of caries, especially in children. Aim: To know the effectiveness of 30% and 38% SDF concentration in preventing caries in children. Method: This Scoping Review was conducted according to Preferres Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and two database (PubMed and Google Scholar). Result: The results showed that the initial search yielded 280 documents. After eliminating duplicate studies and screening full-text articles for eligibility (n = 63), the authors identified 5 studies that met the criteria for inclusion. Conclusion: The concentration of 30% and 38% SDF have the same effectiveness that can prevent the caries of teeth in children SDF 38% has the effectiveness in high antibacterial towards cariogenic biofilm.